2010
DOI: 10.1074/jbc.m110.123612
|View full text |Cite
|
Sign up to set email alerts
|

p38 Regulates Expression of Osteoblast-specific Genes by Phosphorylation of Osterix

Abstract: Osterix, a zinc finger transcription factor, is specifically expressed in osteoblasts and osteocytes of all developing bones. Because no bone formation occurs in Osx-null mice, Osterix is thought to be an essential regulator of osteoblast differentiation. We report that, in several mesenchymal and osteoblastic cell types, BMP-2 induces an increase in expression of the two isoforms of Osterix arising from two alternative promoters. We identified a consensus Sp1 sequence (GGGCGG) as Osterix binding regions in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 56 publications
5
110
0
Order By: Relevance
“…Finally, we considered if the pool of phosphorylated kinase over total kinase changed according to DMSO; once again there were no significant DMSO-related changes within 30 h. Furthermore, experiments with inhibitors of these pathways at appropriate concentrations did not suggest a role for the following inhibitors and pathways in the DMSO effect: U0126 for the ERK1/2 pathway, SB203580 for the p38 MAPK pathway, and Ly-294002 for the PI3K/AKT pathway. The p38 MAPK inhibitor SB203580 is reported to inhibit osteoblast gene activation through phosphorylation of osterix (19). Consistent with this observation, SB203580 decreased ALP activity in a dose-dependent manner in MC3T3-E1 cells grown in OM; however, the DMSO enhancement was still proportional to the reduced ALP activity (Fig.…”
Section: ϫ7supporting
confidence: 76%
“…Finally, we considered if the pool of phosphorylated kinase over total kinase changed according to DMSO; once again there were no significant DMSO-related changes within 30 h. Furthermore, experiments with inhibitors of these pathways at appropriate concentrations did not suggest a role for the following inhibitors and pathways in the DMSO effect: U0126 for the ERK1/2 pathway, SB203580 for the p38 MAPK pathway, and Ly-294002 for the PI3K/AKT pathway. The p38 MAPK inhibitor SB203580 is reported to inhibit osteoblast gene activation through phosphorylation of osterix (19). Consistent with this observation, SB203580 decreased ALP activity in a dose-dependent manner in MC3T3-E1 cells grown in OM; however, the DMSO enhancement was still proportional to the reduced ALP activity (Fig.…”
Section: ϫ7supporting
confidence: 76%
“…In addition, BMP2 promotes osteoblastic differentiation in several cell types, such as multipotent myoblastic C2C12 cells, preosteoblastic MC3T3-E1 cells, primary calvarial osteoblasts, and bone marrow stromal cells. (9,21,30) BMP2 has been reported to activate ERK and p38 MAP kinases in the multipotent C2C12 cells, (11,38) and mainly activates JNK and p38 MAP kinases in MC3T3-E1 cells. (13) A previous study mentioned that JNK2 is mainly activated in the presence of osteogenic supplements (ascorbic acid, b-glycerophosphate, and dexamethasone).…”
Section: Discussionmentioning
confidence: 98%
“…(13,(30)(31)(32) Cells were stimulated with BMP2 in serumfree medium, and the involvement of JNK1 in regulating osteoblastic differentiation was investigated. We found that under such conditions, BMP2 induced ALP activity and JNK inhibition increased it similar to the results in serum-containing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several reports have also indicated that the p38 pathway regulates the expression and activation of critical transcription factors implicated in osteoblastogenesis, i.e., Dlx5, Runx2, and Osx [5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%